Direct liquefaction of pistachio nut shells-Effects of parameters on product yields - KARACA ALBAYRAK, FATMA (TAYLOR & FRANCIS INC, 2017)
Direct liquefaction is a technique for obtaining clean biofuel from biomass in the presence of a solvent at moderate conditions. The aim of this work was to investigate the effects of various experimental parameters on direct liquefaciton yields of a biomass waste material, namely, pistachio nut shells. Experiments were carried out in an autoclave at the conditions of temperature range 300-400 degrees C, pressure 10-30 atmosphere, and tetralin to solvent mixture ratio 0/1-1/1. A Box-Behnken experimental design was used fixing the liquefaction period to 45 min. The effects of these parameters on oil+gas, asphaltene, and preasphaltene yields and total conversion as dependent variables were evaluated, and the model equations for these dependent variables were obtained. Desirability function was used to find the optimal solution for the liquefaction process. Fourier-transform infrared analysis and heating values were also determined for the oil and solid products obtained at the conditions where the maximum oil+gas yield was obtained.
Keywords: Biomass; desirability function; experimental design; liquefaction; pistachio nut shell; PYROLYSIS CONDITIONS